Potential Natural Products Against Respiratory Viruses: A Perspective to Develop Anti-COVID-19 Medicines - Marzieh Omrani; Mohsen Keshavarz; Samad Nejad Ebrahimi; Meysam Mehrabi; Lyndy J. McGaw; Muna Ali Abdalla; Parvaneh Mehrbod (Frontiers Media S.A., 2021)
The emergence of viral pneumonia caused by a novel coronavirus (CoV), known as the 2019 novel coronavirus (2019-nCoV), resulted in a contagious acute respiratory infectious disease in December 2019 in Wuhan, Hubei Province, China. Its alarmingly quick transmission to many countries across the world and a considerable percentage of morbidity and mortality made the World Health Organization recognize it as a pandemic on March 11, 2020. The perceived risk of infection has led many research groups to study COVID-19 from different aspects. In this literature review, the phylogenetics and taxonomy of COVID-19 coronavirus, epidemiology, and respiratory viruses similar to COVID-19 and their mode of action are documented in an approach to understand the behavior of the current virus. Moreover, we suggest targeting the receptors of SARS-CoV and SARS-CoV-2 such as ACE2 and other proteins including 3CLpro and PLpro for improving antiviral activity and immune response against COVID-19 disease. Additionally, since phytochemicals play an essential role in complementary therapies for viral infections, we summarized different bioactive natural products against the mentioned respiratory viruses with a focus on influenza A, SARS-CoV, MERS, and COVID-19.Based on current literature, 130 compounds have antiviral potential, and of these, 94 metabolites demonstrated bioactivity against coronaviruses. Interestingly, these are classified in different groups of natural products, including alkaloids, flavonoids, terpenoids, and others. Most of these compounds comprise flavonoid skeletons. Based on our survey, xanthoangelol E (88), isolated from Angelica keiskei (Miq.) Koidz showed inhibitory activity against SARS-CoV PLpro with the best IC50 value of 1.2 μM. Additionally, hispidulin (3), quercetin (6), rutin (8), saikosaponin D (36), glycyrrhizin (47), and hesperetin (55) had remarkable antiviral potential against different viral infections. Among these compounds, quercetin (6) exhibited antiviral activities against influenza A, SARS-CoV, and COVID-19 and this seems to be a highly promising compound. In addition, our report discusses the obstacles and future perspectives to highlight the importance of developing screening programs to investigate potential natural medicines against COVID-19.